Anterior alveolar dimensions among different classifications of sagittal jaw relationship in Saudi subjects - Adel AlHadlaq (Elsevier, 2010)
Sound orthodontic movement of anterior teeth is delineated by the biological dimensions of the anterior alveolus. Objective: To establish and compare the anterior alveolar dimensions among normal and abnormal sagittal maxillomandibular relationships in a Saudi sample. Materials and methods: The lateral cephalometric radiographs of 81 Saudi subjects (42 males and 39 females) were used to determine the anteroposterior and vertical dimensions of the anterior alveolus in Class I (N = 30), Class II (N = 24), and Class III (N = 27) cases. The anterior alveolar dimensions were then compared among males and females belonging to the same sagittal classification and between the different sagittal classifications of the same gender. Results: Significant differences (P < 0.05) in the anterior alveolar dimensions between males and females were demonstrated for the same sagittal jaw classification. Also, significant differences (P < 0.05) were detected between the anterior alveolar dimensions among the different sagittal maxillomandibular classifications of the same gender. Conclusion: Both the gender and the sagittal maxillomandibular relationship can affect the anteroposterior and vertical dimensions of the anterior alveolus. Keywords: Anterior alveolus, Class I occlusion, Class II malocclusion, Class III malocclusion, Saudi sample